The effect debt, equity on cost of capital among consumer sector, trading sector, and finance sector during economic crisis and after economic crisis / Siti Norsuriani Ab Rahman - Ab Rahman, Siti Norsuriani (2006)
The optimal capital structure is important to the board of director. It is because the best selections of capital structure were giving the good effect to the company. The capital structure is the funds that company uses to finance their activities. However the choosing of capital structure will depends on the cost of capital and others factors. This study especially tries to examine the effect capital structure on cost of capital based on the three main sectors that listed in Kuala Lumpur Stock Exchange (KLSE). The time period for the analysis is the 1996 to 2004. The primary objectives of this study are to known the effect or relationship capital structure on cost of capital. This study identified the capital structure as dependent variable and cost of capital as independent variables. Regression model and Spearman correlation were used to test the research hypotheses. The major finding shows that trading sector and consumer sectors were have the relationship with the debt and cost of capital during economic crisis. However, after economic crisis only consumer sectors were have the relevant result to the debt and cost of capital. So, the overall result shows that only consumer sector have the best result. Instead, the finance sectors insignificant with this hypotheses.